2009
DOI: 10.3174/ajnr.a1869
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Venous Thrombosis: Diagnostic Accuracy of Combined, Dynamic and Static, Contrast-Enhanced 4D MR Venography

Abstract: BACKGROUND AND PURPOSE: MR including MRV is an established method to diagnose CVT. However, it remains unsettled which MR imaging modalities offer the highest diagnostic accuracy. We evaluated the accuracy of a combined, dynamic (1.5 seconds per dataset) and static (voxel size, 1.1 ϫ 0.9 ϫ 1.5 mm), contrast-enhanced MRV method (combo-4D MRV) relative to other established MR/MRV modalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
5

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 23 publications
(32 reference statements)
2
63
0
5
Order By: Relevance
“…© 2011 American Heart Association, Inc. [2,10,42,70,71,73,74,91,[98][99][100]105,106,108,[113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128] 。随着血栓的演变, 静脉窦内出现脱氧血红蛋白和氧化血红蛋白的顺磁 性代谢产物。此时硬膜窦或静脉内血栓在梯度回波 和磁敏感加权磁共振成像上呈低信号 [70,119,129] [196,197,209] 。 几项研究报告了 CVT 病人抽搐发作的发生率和 特征。一项研究报道 [218] ,在 91 例病人中,32% 以 抽搐发作就诊, 2% 在住院期间出现抽搐发作, 仅 9.5% 出现晚期抽搐发作,此外,抽搐发作并不是 1 年预 后的预测指标。早期抽搐发作在有 CT/MRI 上脑实 质病变的病人中发生的可能性高达 3.7 倍 (95% CI 1.4-9.4) 而在有感觉缺失的病人中的可能性增加 7.8 倍 (95% CI 0.8-74.8)。来自 ISCVT 的一项更近的报 告 [197] 显示,624 例病人中的 245 例 (39%) 以抽搐发 作就诊,而 43 例 (6.9%) 在诊断后 2 周内出现早期 抽搐发作。除了就诊时抽搐发作,仅诊断时 CT/MRI 上有幕上脑实质病变 ( 见于 58%) 与早期抽搐发作的 发生有关 (OR 3.1, 95% CI 1.6-9.6)。此外,在有幕上 病变而起病时没有抽搐发作的病人中,应用抗癫痫 药物可使 2 周内抽搐发作的风险降低 70%,尽管这 并没有统计学上的显著性 (OR 0.3, 95% CI 0.04-2.6)。 在这些结果的基础上,作者建议对表现为抽搐发作 的有幕上病变的急性 CVT 病人使用抗癫痫药物 [197] 。 脑积水 上矢状窦和横窦是通过横跨静脉窦壁突入到 蛛网膜下腔并引流到静脉系统的高度血管化结构的 蛛网膜颗粒进行脑脊液 (CSF) 吸收的主要部位。在 CVT,蛛网膜颗粒的功能可能受到障碍,潜在地导 致 CSF 吸收的衰竭和交通性脑积水 (6.6%) [14,198] 。 梗阻性脑积水是 CVT 的一个少见的并发症,可 由出血破入脑室系统所致。通常与累及大脑内静脉的 血栓有关,还可以与丘脑出血有关。此综合征在新生 儿已有很好的描述但可以发生在所有年龄组 …”
Section: Reviewer Disclosuresunclassified
See 2 more Smart Citations
“…© 2011 American Heart Association, Inc. [2,10,42,70,71,73,74,91,[98][99][100]105,106,108,[113][114][115][116][117][118][119][120][121][122][123][124][125][126][127][128] 。随着血栓的演变, 静脉窦内出现脱氧血红蛋白和氧化血红蛋白的顺磁 性代谢产物。此时硬膜窦或静脉内血栓在梯度回波 和磁敏感加权磁共振成像上呈低信号 [70,119,129] [196,197,209] 。 几项研究报告了 CVT 病人抽搐发作的发生率和 特征。一项研究报道 [218] ,在 91 例病人中,32% 以 抽搐发作就诊, 2% 在住院期间出现抽搐发作, 仅 9.5% 出现晚期抽搐发作,此外,抽搐发作并不是 1 年预 后的预测指标。早期抽搐发作在有 CT/MRI 上脑实 质病变的病人中发生的可能性高达 3.7 倍 (95% CI 1.4-9.4) 而在有感觉缺失的病人中的可能性增加 7.8 倍 (95% CI 0.8-74.8)。来自 ISCVT 的一项更近的报 告 [197] 显示,624 例病人中的 245 例 (39%) 以抽搐发 作就诊,而 43 例 (6.9%) 在诊断后 2 周内出现早期 抽搐发作。除了就诊时抽搐发作,仅诊断时 CT/MRI 上有幕上脑实质病变 ( 见于 58%) 与早期抽搐发作的 发生有关 (OR 3.1, 95% CI 1.6-9.6)。此外,在有幕上 病变而起病时没有抽搐发作的病人中,应用抗癫痫 药物可使 2 周内抽搐发作的风险降低 70%,尽管这 并没有统计学上的显著性 (OR 0.3, 95% CI 0.04-2.6)。 在这些结果的基础上,作者建议对表现为抽搐发作 的有幕上病变的急性 CVT 病人使用抗癫痫药物 [197] 。 脑积水 上矢状窦和横窦是通过横跨静脉窦壁突入到 蛛网膜下腔并引流到静脉系统的高度血管化结构的 蛛网膜颗粒进行脑脊液 (CSF) 吸收的主要部位。在 CVT,蛛网膜颗粒的功能可能受到障碍,潜在地导 致 CSF 吸收的衰竭和交通性脑积水 (6.6%) [14,198] 。 梗阻性脑积水是 CVT 的一个少见的并发症,可 由出血破入脑室系统所致。通常与累及大脑内静脉的 血栓有关,还可以与丘脑出血有关。此综合征在新生 儿已有很好的描述但可以发生在所有年龄组 …”
Section: Reviewer Disclosuresunclassified
“…By the second week, thrombus contains methemoglobin, which results in hyperintensity on T1-and T2-weighted images ( Figure 5). 2 70,119,129 The principal early signs of CVT on non-contrast-enhanced MRI are the combination of absence of a flow void with alteration of signal intensity in the dural sinus. MRI of the brain is suggestive of CVT by the absence of a fluid void signal in the sinus, T2 hypointensity suggestive of a thrombus, or a central isodense lesion in a venous sinus with surrounding enhancement.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there exist new, promising MRA techniques such as time-resolved MRA [59,60], which might further improve the value of MR for the evaluation of the cerebral veins and sinuses. A very recent study on 20 CVST patients and 19 controls demonstrated that the combination of a dynamic and a static three-dimensional combined MR venography -the so-called combo 4-D MRV -was superior to TOF-MRA [61]. Future studies should address the potential value of these sequences as well as the impact of higher field strengths for the diagnosis of CVST.…”
Section: Venous Mra Techniquesmentioning
confidence: 99%
“…The diagnosis must be confi rmed with gradient-echo techniques or MR angiography. Phasecontrast or Gd-enhanced time-of-fl ight MRAs are the preferred techniques because they are not adversely affected by intraluminal clot [ 2 ]. Associated parenchymal infarcts are found in the areas of venous abnormalities, and the infarcts are often hemorrhagic because arterial perfusion is maintained to the damaged tissue.…”
Section: Venous/sinus Occlusionmentioning
confidence: 99%